Effects of exercise interventions on negative emotions, cognitive performance and drug craving in methamphetamine addiction - Xu, Conghui; Zhang, Zunyue; Hou, Dezhi; Wang, Guangqing; Li, Congbin; Ma, Xingfeng; Wang, Kunhua; Luo, Huayou; Zhu, Mei (Frontiers in Psychiatry, 2024)
Introduction Methamphetamine is currently one of the most commonly used addictive substances with strong addiction and a high relapse rate. This systematic review aims to examine the effectiveness of physical activity in improving negative emotions, cognitive impairment, and drug craving in people with methamphetamine use disorder (MUD). Methods A total of 17 studies out of 133 found from Embase and PubMed were identified, reporting results from 1836 participants from MUD populations. Original research using clearly described physical activity as interventions and reporting quantifiable outcomes of negative mood, cognitive function and drug craving level in people with MUD were eligible for inclusion. We included prospective studies, randomized controlled trials, or intervention studies, focusing on the neurological effects of physical activity on MUD. Results Taken together, the available clinical evidence showed that physical activity-based interventions may be effective in managing MUD-related withdrawal symptoms. Discussion Physical exercise may improve drug rehabilitation efficiency by improving negative emotions, cognitive behaviors, and drug cravings. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024530359.